2010
DOI: 10.1089/pho.2008.2242
|View full text |Cite
|
Sign up to set email alerts
|

Use of 660-nm Diode Laser in the Prevention and Treatment of Human Oral Mucositis Induced by Radiotherapy and Chemotherapy

Abstract: Laser therapy was effective in preventing and treating oral effects induced by radiotherapy and chemotherapy, thus improving the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 12 publications
(15 reference statements)
0
43
1
15
Order By: Relevance
“…LPT is based on nonthermal effects of light on biological tissues, and its use in the prevention and treatment of mucositis induced by antineoplastic treatment has presented promising results, especially in clinical studies (1,3,4,13). The effect of LPT is based on its ability to modulate several metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LPT is based on nonthermal effects of light on biological tissues, and its use in the prevention and treatment of mucositis induced by antineoplastic treatment has presented promising results, especially in clinical studies (1,3,4,13). The effect of LPT is based on its ability to modulate several metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Zanin et al (1) and Lopes et al (17) reported that in their studies all patients under RT who received LPT completed the planned RT treatment, whereas patients not treated with LPT had to interrupt the RT because of decreased immunity caused by secondary asthenia and deglutition difficulties, which impacted their survival. Several protocols have been used for treating oral mucositis and the observed results sometimes differ (1,3,4,13,16,17). It is necessary to standardize the protocols for prevention and treatment of this condition in order to make different studies comparable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ils rapportent un meilleur contrôle de l'intensité de la douleur avec le laser de plus faible énergie avec un protocole de 3 fois/semaine. Zanin et al (2009) ont obtenu des résultats similaires avec un laser diode 660 nm utilisé 2 fois/semaine, dans une étude portant sur 72 patients (groupe laser versus groupe contrôle (n = 36)) [16].…”
Section: Commentairesunclassified